Preconception Counseling for Women With Diabetes - Hubberd, Abegail L. (Clin Diabetes, 2020)
“Quality Improvement Success Stories” are published by the American Diabetes Association in collaboration with the American College of Physicians, Inc., and the National Diabetes Education Program. This series is intended to highlight best practices and strategies from programs and clinics that have successfully improved the quality of care for people with diabetes or related conditions. Each article in the series is reviewed and follows a standard format developed by the editors of Clinical Diabetes. The following article describes the efforts of a U.S. Airforce diabetes specialty clinic to improve the delivery of preconception counseling to women with diabetes who are of childbearing potential.